Measurement of psychological entitlement in 28 countries - Magdalena Żemojtel-Piotrowska; Jarosław Piotrowski; Jan Cieciuch; Rachel M Calogero; Alain Van Hiel; Piergiorgio Argentero; Sergiu Bălţătescu; Piergiorgio Argentero; Tomasz Baran; Gopa Bhardwaj; Marcin Bukowski; Melania Chargazia; et al. (European Association of Psychological Assessment, Hogrefe, 2015)
This article presents the cross-cultural validation of the Entitlement Attitudes Questionnaire, a tool designed to measure three facets of psychological entitlement: active, passive, and revenge entitlement. Active entitlement was defined as the tendency to protect individual rights based on self-worthiness. Passive entitlement was defined as the belief in obligations to and expectations toward other people and institutions for the fulfillment of the individual’s needs. Revenge entitlement was defined as the tendency to protect one’s individual rights when violated by others and the tendency to reciprocate insults. The 15-item EAQ was validated in a series of three studies: the first one on a general Polish sample (N = 1,900), the second one on a sample of Polish students (N = 199), and the third one on student samples from 28 countries (N = 5,979). A three-factor solution was confirmed across all samples. Examination of measurement equivalence indicated partial metric invariance of EAQ for all national samples. Discriminant and convergent validity of the EAQ was also confirmed.